Akty wiary - Segal, Erich, 1937-; Zychowicz, Elzbieta; Nowakowski, Witold (Warszawa : Albatros, 1999)
Polish translation of "Acts of Faith". A story of three youths seeking Faith. A love story of forbidden love, sin and redemption.
Translation of: Acts of faith.
Keywords: Faith -- Fiction